PENGARUH PEMBERIAN TUMMY TIME EXERCISE TERHADAP PENINGKATAN KEMAMPUAN GROSS MOTORIC HEAD CONTROL AND ROLLING PADA ANAK USIA 0-16 MINGGU - Widodo, Agus; Rizky, Rima; Waspada, Edy (Prosiding University Research Colloquium, 2018)
Background: Lifting your head and rolling ability are the first motorbike abilities for babies. If not, the prone period takes a long time. This period is important in subsequent development. As for one form of stimulation to improve motor skills to lift the baby's head is by tummy time exercise. Objective: To determine the effect of tummy time exercise on increasing motor ability to lift the head in children aged 0-16 weeks. Research Method: This type of research design is a quasi experiment with non-randomized two groups approach method pre-test and post-test design. Subjects were divided into two groups, treatment groups were given tummy time exercise, while the control group was not given tummy time exercise. Measurement of pretest and posttest using a stopwatch. Test for normality using the Shapiro Wilk Test, test the effect of using Paired Sample t-Test, different test effects using the Independent Sample t-Test. Results of the study: The results of statistical tests were obtained to determine the effect of tummy time exercise using Paired Sample T-Test on the age group 0-4 weeks obtained p value was p <0.05 (p = 0.003) and t count = -18.860 and t table = 12 , 70620 then t count> t table. So there is a significant effect of tummy time exercise on increasing motor ability to lift the head based on the length of the head lift. Conclusion: There is an effect of tummy time exercise on increasing motor ability to lift the head in children aged 0-16 weeks.